2021
DOI: 10.1186/s12913-021-06354-y
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative systematic review and thematic synthesis exploring the impacts of clinical academic activity by healthcare professionals outside medicine

Abstract: Background There are increasing opportunities for healthcare professionals outside medicine to be involved in and lead clinical research. However, there are few roles within these professions that include time for research. In order to develop such roles, and evaluate effective use of this time, the range of impacts of this clinical academic activity need to be valued and understood by healthcare leaders and managers. To date, these impacts have not been comprehensively explored, but are sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 40 publications
3
39
0
4
Order By: Relevance
“…24 The research team comprised postdoctoral clinicians from nursing and physiotherapy disciplines with previous qualitative research experience. Qualitative semistructured 1:1 interviews were conducted using prepiloted topic guides which were informed by our systematic review of the literature 13 (online supplemental file 1). The COREQ checklist (COnsolidated criteria for REporting Qualitative research) was used to guide reporting.…”
Section: Design and Approvalsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The research team comprised postdoctoral clinicians from nursing and physiotherapy disciplines with previous qualitative research experience. Qualitative semistructured 1:1 interviews were conducted using prepiloted topic guides which were informed by our systematic review of the literature 13 (online supplemental file 1). The COREQ checklist (COnsolidated criteria for REporting Qualitative research) was used to guide reporting.…”
Section: Design and Approvalsmentioning
confidence: 99%
“…Our recent systematic review explored the impacts of NMAHPP clinical academic activity reported in the literature and used the VICTOR framework to categorise the identified impacts. 13 Across all categories, there were three recurring sub-themes: the challenges and benefits of balancing clinical and academic roles; creation and implementation of new evidence; and collaboration and networks. The first two of these subthemes were also reflected in the current study, suggesting that these are likely to be important features in developing clinical academic careers and areas where impact could be assessed.…”
Section: Open Accessmentioning
confidence: 99%
“…Noen år etter ferdig PhD ble de konkurrerende krav fra akademi og klinikk for krevende og jeg valgte å gå over til akademiet på fulltid. Leder for forskere som kombinerer klinisk arbeide og forskning, og forskerne selve, opplever positive utfall for både pasienter og organisasjonen som: evidensbasert behandling, pasient involvering og attraktiv arbeidsplass for personalen (Newington et al, 2021). Det er et synkende antall personer som kontinuerlig arbeider i klinikk og i akademi samtidig, på grunn av de krav som det innebaerer for den enkelte (Bostwick, 2012;de Groot et al, 2020).…”
Section: Erfaring Av Balansen Mellom Klinisk Arbeid Og Forskningunclassified
“…I dette smeltepunktet mellom det som vi kan og forstår og det en annen kan og forstår, er det ikke kun risiko for misforståelse, det er samtidig mulighet for kreativitet og samskapning av forskningsprosjekter som leder til holdbar forbedring. Når klinisk virksomt hos personell er involvert i forskning og vice versa det er det en rekke fordeler: økt klinisk relevans av forskningsspørsmål, tilgang til kliniske innstillinger for forskning, kliniske ekspertise og innsideperspektiv til forskningen, forskere som er klarert av deltakerne som kan oppmuntre til deltakelse, og å ha forskere som er motivert til å spre og anvende aktuelle funn og fortsette sin forpliktelse til de undersøkte (Barry et al, 2019;Barry et al, 2020;Hay-Smith et al, 2016;Newington et al, 2021).…”
Section: Erfaring Av Balansen Mellom Klinisk Arbeid Og Forskningunclassified
See 1 more Smart Citation